Comparison of Global and Regional Compliance-Guided Positive End-Expiratory Pressure Titration on Regional Lung Ventilation in Moderate-to-Severe Pediatric Acute Respiratory Distress Syndrome - Ren, Hong; Xie, Li; Wang, Zhulin; Tang, Xiaoliao; Ning, Botao; Teng, Teng; Qian, Juan; Wang, Ying; Fu, Lijun; Zhao, Zhanqi; Xiang, Long (Frontiers in Medicine, 2022)
Purpose: To investigate the difference of PEEP selected with chest electrical impedance tomography (EIT) and with global dynamic respiratory system compliance (Crs) in moderate-to-severe pediatric acute respiratory distress syndrome (pARDS). Methods: Moderate-to-severe pARDS (PaO2/FiO2<200 mmHg) patients were retrospectively included. On the day of ARDS diagnosis, two PEEP levels were determined during decremental PEEP trial for each individual using the best compliance (PEEPC) and EIT-based regional compliance (PEEPEIT) methods. The differences of global and regional compliance (for both gravity-dependent and non-dependent regions) under the two PEEP conditions were compared. In addition, the EIT-based global inhomogeneity index (GI), center of ventilation (CoV), and standard deviation of regional delayed ventilation (RVDSD) were also calculated and compared. Results: A total of 12 children with pARDS (5 with severe and 7 with moderate pARDS) were included. PEEPC and PEEPEIT were identical in 6 patients. In the others the differences were only ±2cmH2O (one PEEP step). There was no statistical differences in global compliance at PEEPC and at PEEPEIT [28.7 (2.84-33.47) vs. 29.74 (2.84-33.47) ml/cmH2O median (IQR), P=0.028 (the significant level after adjusted for multiple comparison was 0.017). Furthermore, no differences were found in regional compliances and other EIT-based parameters measuring spatial and temporal ventilation distributions. Conclusions: Although EIT provided information of ventilation distribution, PEEP selected with best Crs might be non-inferior to EIT-guided one regarding to regional ventilation in moderate-to-severe pARDS. Further study with large sample size is required to confirm the finding.